MR-guided focused ultrasound robot for performing experiments on large animals - Mylonas, N.; Damianou, Christakis A. (My University, 2011)
Introduction: In this paper an experimental MRI-guided focused ultrasound robot for large animals is presented. Materials and methods: A single element spherically focused transducer of 4 cm diameter, focusing at 10 cm and operating at 1 MHz was used. A positioning device was developed in order to scan the ultrasound transducer for performing MR-guided focused ultrasound experiments in large animals such as pig, sheep and dog. The positioning device incorporates only MRI compatible materials such as piezoelectric motors, Acrylonitrile Butadiene Styrene (ABS) plastic, brass screws, and brass pulleys. The system is manufactured automatically using a rapid prototyping system. Results: The system was tested successfully in a number of animals for various tasks (creation of single lesions, creation of overlapping lesions, and MR compatibility). Conclusions: A simple, cost effective, portable positioning device has been developed which can be used in virtually any clinical MRI scanner since it can be sited on the scanner's table. The propagation of HIFU can be via a lateral or superior-inferior approach. This system has the potential to be marketed as a cost effective solution for performing experiments in small and large animals. © 2011 American Institute of Physics.
Keywords: MR-guided | MRI | Positioning | Robot | Ultrasound